Pengembangan Bahan Ajar Matematika dengan Memanfaatkan Geogebra untuk Meningkatkan Pemahaman Konsep - Indri Lestari (Universitas Serang Raya, 2018)
This study aims to find out the characteristics of the appropriate book for improving understanding of mathematical concepts, especially on the subject of function by utilizing Geogebra program. The research method used is research and development, where the research is intended to develop and produce certain products, and test the effectiveness of these products. Subjects in this study were students of SMP Negeri 6 in the city of Serang with a limited scale test conducted on 5 students, while field tests were conducted on 15 students. The conclusions developed in this study that use the teaching materials by utilizing Geogebra program have improved conceptual understanding compared with the students before using the teaching materials.